The misalignment of exchange rates in Malaysia: Evidence using FEERs model - Shukri, J. Mohamad; Habibullah, Muzafar Shah; Sanusi, Nur Azura (2015)
The misalignment of exchange rate is the normal phenomenon in currency’s behaviour for a country. The traditional theory of exchange rates in determining the misalignment of the currency is the Law of One Price (henceforth LOP), where the price levels would be the same between two countries after converting their price into a common currency.However, this model does not take into account the economically interesting question of whether a particular exchange rate is driven by macroeconomics fundamentals.Therefore, the aim of this paper is to investigates the behaviour of exchange rate movement in Malaysia and identify the determinants of macroeconomics fundamentals on the exchange rates for this country.By using fundamental equilibrium exchange rates (FEERs) model, this study adopts the autoregressive distributed lag (ARDL) to examine the long run relationships (or cointegration) among the variables and the dynamic effect within variables in the short run.